14 Differential effects of exercise and nitrates on invasive haemodynamics in patients with coronary artery disease. (25th January 2018) - Patterson, Tiffany; Rivolo, Simone; Burkhoff, Daniel; Schreuder, Jan; Briceno, Natalia; Arri, Satpal; Asrress, Kal; Williams, Rupert; Clapp, Brian; Kapetenakis, Stam; Perera, Divaka; Marber, Mike; et al.
Abstract : Background: Exertional angina and the response to nitrates have been recognised for over two centuries. This ischaemic cascade and the mechanistic relief by nitrates has not been extensively studied. The aim was to identify these precise haemodynamic changes. Methods: In 31 patients with exertional angina and coronary artery disease, real-time simultaneous LV pressure-volume (PV) relations and invasive measures of coronary flow were performed in the cathlab. A novel software system was developed to analyse these simultaneous data. Results: Compared to control, exercise induced ischaemia (supine cath lab ergometer) led to a rightward, upward shift in end-systolic (39±14 versus 71±31 mL; p<0.001) and end-diastolic (90±28 vs 109±31 mL; p<0.05) PV relations, decreased cardiac output (7±2.3 versus 4.5±1.9; p<0.05) and impaired ventricular-arterial (VA) interaction (SVR 24±17 vs 44±18 mmHg.min/L; p<0.05). Nitrates induced an opposing effect with leftward, downward shift of end-systolic and diastolic PV relations, reduced cardiac work (1.2±0.4 versus 1.5±0.5 J; p<0.001) thus myocardial oxygen consumption, enhanced VA interaction and induced coronary stenosis dilatation (2.7±3.6 versus 4.4±3.3 mmHg/cm/sec; p<0.01). Conclusions: These data support the adverse haemodynamic consequences of ischaemia and the systemic and coronary vasodilatory effects of nitrates. The novel technology developed and used to assess real-time ventricular-arterial interaction has the potential to facilitate future works investigating haemodynamic change induced by disease states and therapeutic interventions.